The Role of Perceived Organizational Support and Organizational Citizenship Behavior in Building Employee Performance - Ali Amran; Egi Achmad Faizal; Yunika Komalasari; Yayu Sri Rahayu; Devi Yuniati Drajat; Rofily Putriyandari (Journal of International Conference Proceedings (JICP), 2022)
The study aims to determine the impact of perceived organizational support and organizational citizenship behavior on performance employees. The method used in this research is a survey method by taking samples of 70. These respondents are taken by using non-probability sampling method with saturated sampling technique. The type of study used in this research is descriptive and verificative survey with multiple regression analysis. The results of the study are the level of perceived organizational support is good, as well as the level of organizational citizenship behavior and performance are good. The hypothesis testing shows that perceived organizational support partially has a positive and significant effect on performance, and organizational citizenship behavior partially has a positive and significant effect on performance. Whereas perceived organizational support and organizational citizenship behavior affect performance simultaneously. The variable that most influences performance is perceived organizational support. The study concludes that perceived organizational support and organizational citizenship behavior are two important predictors to build employee performance. This is useful for the company in building performance by increasing perceived organizational support and good organizational citizenship behavior. Keywords: Organizational Citizenship Behavior, Perceived Organizational Support, Performance.